2009
DOI: 10.1111/j.1460-2695.2009.01402.x
|View full text |Cite
|
Sign up to set email alerts
|

Brittle fracture evaluation of a fine grain cement mortar in combined tensile‐shear deformation

Abstract: A B S T R A C T Different laboratory experiments are usually conducted to characterize the fracture behaviour and integrity properties of newly developed structural materials. However, the reported fracture tests data for an improved high strength cement mortar (HSCM) under combined tension-shear loading are not in agreement with theoretical predictions obtained from well-known fracture criteria. It is shown in this paper that the significant difference existing between the experimental and theoretical results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…Fracture toughness is a measure of material resistance to crack growth and can be obtained experimentally using suitable test configurations. Researchers have frequently used disk type specimens such as the cracked semi-circular bend (SCB) specimens subjected to flexural bending and center cracked Brazilian disk (BD) specimens subjected to diametral compression to conduct mixed mode fracture experiments on various rock materials [1][2][3][4][5][6][7][8][9][10]. Both specimens have simple shapes and only require conventional loading apparatus.…”
Section: Introductionmentioning
confidence: 99%
“…Fracture toughness is a measure of material resistance to crack growth and can be obtained experimentally using suitable test configurations. Researchers have frequently used disk type specimens such as the cracked semi-circular bend (SCB) specimens subjected to flexural bending and center cracked Brazilian disk (BD) specimens subjected to diametral compression to conduct mixed mode fracture experiments on various rock materials [1][2][3][4][5][6][7][8][9][10]. Both specimens have simple shapes and only require conventional loading apparatus.…”
Section: Introductionmentioning
confidence: 99%
“…2 Further propagation of such cracks may occur because of tensile thermal stresses induced by temperature fluctuation which can result in pure mode I fracture mechanism in the asphalt pavement. Different test specimens such as the single edge notched three-point bend beam (SENB), [9][10][11][12][13][14][15] rectangular beam subjected to four-point bend loading, 16,17 disc shape compact tension (DCT), [18][19][20] centre cracked diametraly compressed Brazilian disc, [21][22][23] wedge splitting specimen, 24 edge notched disc bend specimen (ENDB) [25][26][27] and also semi-circular bend (SCB) 3,5,6, [28][29][30][31][32][33][34][35] have been used in the past for determining the fracture properties in a wide range of asphalt concrete materials including hot mix asphalt (HMA), warm mix asphalt (WMA) and other types of cement or polymer concretes. [3][4][5][6] In recent years, numerous papers have been published for studying the low temperature cracking behaviour of asphalt materials and determining the fracture toughness of asphalt concretes using either experimental, theoretical or modelling methods.…”
Section: Introductionmentioning
confidence: 99%
“…Various test specimens have been used in the past for mixed mode fracture experiments. The edge cracked beam subjected to three or four point bend loading [1], the compact tension-shear specimen [2], the center cracked circular disk (CCCD) specimen [3], the cracked semi-circular specimen under three-point bending [4] and the edge cracked triangular specimen [5] under three point bending are some of the specimens used frequently for mixed mode fracture tests on rocks. The experimental results in previous studies have indicated that the values of fracture resistance obtained from these test configurations depend significantly on the specimen type not only in pure mode I, but also in mixed mode loading.…”
Section: Introductionmentioning
confidence: 99%